[PP.18.22] EFFECTS OF MOXONIDINE AND LOW CALORIE DIET IN YOUNG OVERWEIGHT MALES. (September 2017) - Lambert, E.; Sari, C.; Head, G.; Grima, M.; Eikelis, N.; Straznicky, N.; Schlaich, M.P.; Dixon, J.; Lambert, G.
Abstract : Objective: Elevated sympathetic nervous system activity in overweight individuals is believed to play a detrimental role in metabolic and cardiovascular health in early adulthood. We therefore aimed to compare the effects of a treatment with either a low calorie diet, a sympatholytic agent or a combination of both on hemodynamic and metabolic parameters and renal and endothelial function. Design and method: Overweight (BMI>25 kg/m 2 ), young (18–30 years) otherwise healthy males were randomly allocated to receive either a low calorie diet (LCD; n=10), moxonidine (MOX; n = 10, 0.4 mg/day), a combination of both (LCD+MOX; n = 11) or to act as controls (CONT; n = 6) for a period of 6 months. Muscle sympathetic nerve activity (MSNA) was measured by microneurography, endothelial function was assessed using digital pulse tonometry and renal function using creatinine clearance derived from the Cockcroft Gault formula before and after intervention. Results: Weight loss occurred in the LCD and LCD+MOX (−7.5 ± 1.9 and −7.6 ± 1.9 kg). MSNA significantly decreased in the LCD, MOX and LCD+MOX groups (−14 ± 3, −14 ± 3, −14 ± 2 bursts per 100 heartbeats) and this was associated with a decrease in systolic blood pressure (−8.9 ± 3.3; −8.8 ± 5.5;−9.8 ± 3.2 mmHg). All other metabolic parameters for both LCD, CON and MOX groups remained unchanged. Endothelial function remained unchanged in all groups. In the LCD + MOX, additional benefits included decreased waist circumference (−8.3 ± 1.9 cm), decreased total cholesterol (−0.78 ± 0.23 mmol/l) and LDL cholesterol (−0.49 ± 0.16 mmol/l) and fasting insulin (−6.5 ± 2.8 mmol/l) and attenuated glomerular hyperfiltration from 187 ± 4 to 167 ± 4 ml/min). Conclusions: The addition of moxonidine to a LCD may have beneficial effects on the metabolic profile and renal function of overweight young males.